Optimising Psychological Well-Being in Chinese-Australian Adolescents: A 24-Hour Movement Guidelines Approach - Wei-Cheng Chao; Asaduzzaman Khan; Jui-Chi Shih; Wen Li; Ching-Lin Wu; Kuan-Chung Chen; Bill Cheng (Children)
Background: Chinese-Australian adolescents face unique academic and cultural challenges that may impact their lifestyle and psychological well-being. Physical activity, screen time, and sleep are known to influence well-being. However, research on the adherence to the 24-Hour Movement Guidelines among Chinese-Australian adolescents remains limited and awaits further investigation. Objective: This study hypothesized a significant positive association between adherence to the 24-Hour Movement Guidelines for physical activity, screen time, and sleep, and the psychological well-being of Chinese-Australian adolescents. Methods: A self-reported questionnaire was distributed to two language schools in Brisbane, Australia, targeting high school students from grades 7 to 12 with Chinese-Australian backgrounds. This study used multiple linear regression modelling to examine the associations between meeting or not meeting recommendations. Meeting the 24-Hour Movement Guidelines was defined as ≥60 min/day of moderate to vigorous physical activity (MVPA), ≤2 h/day of recreational screen time, and 9–11 h/night of sleep. Results: Out of 251 participants (average age: 13.31 years; 58% female), only 20.3% met two or three recommendations, while 43.3% met one, and 36.2% met none. The most common compliance was meeting only the screen time guideline alone (48%), while 9.6% met either MVPA + screen time or screen time + sleep. The regression analysis showed that meeting at least MVPA (β = 1.41, 95% CI: 0.07 to 2.74) or at least sleep (β = 1.40, 95% CI: 0.19 to 2.60) was associated with better psychological well-being. Notably, meeting MVPA and sleep guidelines was significantly associated with higher well-being (β = 3.83, 95% CI: 1.06–6.60). From the results, adherence to additional 24-Hour Movement Guidelines was associated with improved psychosocial well-being. However, a small proportion of adolescents met all the guidelines. Conclusions: Greater adherence to physical activity and sleep guidelines is linked to better psychological well-being among Chinese-Australian adolescents. These results highlight the importance of promoting healthy behaviours and implementing public health strategies to enhance education on exercise and sleep, particularly at the school and family levels, to support adolescents’ psychological well-being.